Risk management in changing benchmark rates regime: Prudential implications for Islamic banks and supervisors - Chattha, Jamshaid Anwar; Syed Jaafar Alhabshi, Syed Musa (IIUM Press, 2017)
Post-global financial crisis scenario has presented extraordinary challenges to the global economy, in general, and the banking industry, in particular. This has brought the financial industry to a set of new challenges including risk management in changing benchmark rates risk for Islamic banks. Thus, in recent years, the management of benchmark rates (or interest rates) received considerable prominence in the banking sector due to a number of reasons including supervision of banks’ benchmark rates under Basel II Pillar II. Taking into account the specific features of Islamic banks, the purpose of the paper is to theoretically and empirically review the possible prudential implications of lowly and increasing benchmark rates risk, and provide a sturdy risk management and regulatory perspective for Islamic banks and supervisors. For low rates perspective, policy rates of 12 central banks were collected and analyzed. However, for increasing rates scenario, we used duration gap and stress testing approaches, with a sample of 50 Islamic banks from 13 countries, for the period 2009-2015. Our empirical results indicate that persistently low benchmark rate regime carries strategic implications for Islamic banks including pressure on profitability, excessive risk taking and distortion in credit allocations. On the other hand, an increasing benchmark rate regime indicates the significant loss of the capital base, emergence of displaced commercial risk causing early withdrawals by the customers due to higher expectations in dual banking systems. This study concludes that implications under both scenarios call for a better risk management with appropriate tools and effective supervisory oversight for Islamic banks.